1995
DOI: 10.1111/j.1432-1033.1995.0148l.x
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidation of Methylamine in Paracoccus denitrificans

Abstract: The in vivo oxidation of methylamine has been studied in Paracoccus denitrificans. Four components are involved in the electron transfer from methylamine to oxygen; methylamine dehydrogenase (MADH), amicyanin, cytochrome c and cytochrome-c oxidase. In P. denitrificans, MADH and its electron acceptor amicyanin are indispensable for growth on methylamine. In the present study, site-directed mutants have been used to demonstrate participation of cytochrome c550 and the aa3-type cytochrome-c oxidase. Moreover, evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Yields on methanol were relatively low compared to those seen with methylamine for both strains S1 and TGA (Table 3). As methanol and methylamine are both dehydrogenated to give formaldehyde (De Gier et al 1995), similar yields would be expected, as observed with other methylotrophs (Goldberg et al 1976;Van Verseveld and Stouthamer 1978;Suylen et al 1986;Wood et al 1998). The less efficient use of methanol cannot yet be explained.…”
Section: Discussionsupporting
confidence: 60%
“…Yields on methanol were relatively low compared to those seen with methylamine for both strains S1 and TGA (Table 3). As methanol and methylamine are both dehydrogenated to give formaldehyde (De Gier et al 1995), similar yields would be expected, as observed with other methylotrophs (Goldberg et al 1976;Van Verseveld and Stouthamer 1978;Suylen et al 1986;Wood et al 1998). The less efficient use of methanol cannot yet be explained.…”
Section: Discussionsupporting
confidence: 60%
“…From pUCpcco a 965‐bp Kpn I– Pst I fragment was cloned into pBK11SL ( Kpn I– Pst I), yielding plasmid pPr271. A 637‐bp Eco RI– Eco RV fragment from pUCc5501, which contained the cta DII promoter [28], was cloned into pBK11 ( Eco RI– Sma I). This pBK11 derivative was named pPr231.…”
Section: Methodsmentioning
confidence: 99%
“…The forward primer contained the nucleotides from positions 79 through 97 of the sequence of the qox locus of P. denitrificans [7] (5 H -CGCCGCAATTGCCACGTTCTCATAGCTGGG), adapted to contain a MunI restriction site (underlined). The reversed one contained the complementary bases from position 710 through 728 (5 H -CCGGCGGATCCGGAAT-CAGCAAGGCAAGCC), adapted with a BamHI restriction pUC19 der., cycA, ctaDII [28] site (underlined). The PCR product was checked by sequence analysis (dna strider 1.0 and geneworks 2.3) and then cloned in pBK11.…”
Section: Dna Manipulations and Mutagenesismentioning
confidence: 99%
“…41 However, the electron-transfer kinetics study 42 and the X-ray structure analysis 43 of MADH complexed with amicyanin and cytochrome c 551 demonstrated that amicyanine shows high specificity for MADH in P. denitrificans. However, Methylomonas sp.…”
Section: Comparison Of the Structures Between Az-iso2 And Amicyaninmentioning
confidence: 97%